Lady Macbeth Mcenskog okruga Dmitrija Šostakoviča u Zagrebu. Prigodna razmišljanja o liku Katarine Izmajlove - Benčić, Živa (Array, 2004)
A recent staging in Zagreb of Dmitri Shostakovich's Lady Macbeth of Mtsensk District, directed by Thomas Schulte-Michels, lead the author to reflect anew upon the character of Katerina Izmailova. The German director has resolved the tragic erotic love theme by using the scene of prisoner's camp as a symbol of jeopardized freedom of an individual. Starting from a view that the idea of deep interconnection of erotic and social freedom of Katerina Izmailova is already implicit in Shostakovich's opera, the author analyzes subversive tendencies of Katerina's eros in the context of totalitarian Soviet society of Stalin's era. In author's opinion, Stalin has condemned this master-piece of opera dramaturgy primarily because in Katerina Izmailova's love passion he saw a great danger of individualism, and in individualism, which disobeys imperatives of the Party and the State, Stalin saw one of the most undesirable phenomena in his regime.